2020
DOI: 10.3390/cancers12102860
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoxia and SRC Tyrosine Kinase in Glioblastoma Invasiveness and Radioresistance

Abstract: Advances in functional imaging are supporting neurosurgery and radiotherapy for glioblastoma, which still remains the most aggressive brain tumor with poor prognosis. The typical infiltration pattern of glioblastoma, which impedes a complete surgical resection, is coupled with a high rate of invasiveness and radioresistance, thus further limiting efficient therapy, leading to inevitable and fatal recurrences. Hypoxia is of crucial importance in gliomagenesis and, besides reducing radiotherapy efficacy, also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 120 publications
0
43
0
Order By: Relevance
“…For this reason, the tumor-treating field is considered as a standard of care in some guidelines [ 107 ]. Moreover, in the last years, the association of molecularly targeted drugs such as tyrosine kinase administration or others combined with X-rays to decrease radioresistance due to hypoxia showed encouraging results [ 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the tumor-treating field is considered as a standard of care in some guidelines [ 107 ]. Moreover, in the last years, the association of molecularly targeted drugs such as tyrosine kinase administration or others combined with X-rays to decrease radioresistance due to hypoxia showed encouraging results [ 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, IR is known to activate the transcription of genes, through the presence of cAMP-responsive elements (CREs) in their promoters, to guide cell fate and survival after radiation exposure [62][63][64]. Finally, it was reported that cancer-associated stress, including hypoxia, chronically activates the bioenergetic sensor AMP kinase (AMPK), as a pro-survival signal [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…No clinical strategy has been approved by the FDA to reduce hypoxia in order to augment standard therapies. Many attempts have been made to increase oxygen delivery to tumors without clinical success [ 34 ]. These failures are partly due to limitations in tumor vessel function.…”
Section: Discussionmentioning
confidence: 99%